What wages do people expect for vocational and academic education backgrounds in Switzerland? - Cattaneo, Maria Alejandra [Verfasser] (My University, 2024)
„Correctly anticipating the earnings for different education profiles is pivotal in making informed education decisions. In this paper, leveraging unique survey data, we study the wage expectations for academic and vocational education backgrounds in Switzerland. Personal reference points matter in forming these wage expectations as we find significant heterogeneity in their distributions by gender, age, socioeconomic status, region of residence, and migration background. Asymmetries exist between beliefs for academic and vocational backgrounds since relative differences in wage expectations also vary by respondents’ characteristics. These heterogeneities are vital for education policy because our analyses show that the wage expectations are associated with preferences for specific educational tracks for the own (hypothetical) child. If education decisions are ill-informed, this possibly leads to educational mismatches and related adverse effects later in life.“ (author’s absract; BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; S 1.4 Hochschulbildung; G 1.2.2.1 Lohn- & Tarifsysteme; 370; 330; Berufsausbildung; Ausbildungsabsolvent; Studium; Hochschulabsolvent; Lohn; Lohnhöhe; Schätzung